Journey into the heart : a tale of pioneering doctors and their race to transform cardiovascular medicine - Monagan, David; Williams, David O. (New York : Gotham Books, 2007)
The twentieth-century journey to understand the human heart was a saga on a par with the race to the moon. Physicians have evolved from fearing to even touch a living human heart to rebuilding and transplanting hearts. Today heart attacks can often be stopped while in progress, and non-invasive surgical techniques eliminate any need for a knife, while clearing vital arteries in minutes. This book traces the quest of the daring pioneers who struggled to solve these medical complexities. Andreas Gruentzig, an East German "child of the rubble," took center stage in revolutionizing cardiovascular care, developing the first tiny balloon-tipped probes in his Zurich apartment. Despite harsh skepticism, Gruentzig demonstrated that his gadgets could transform the lives of millions. Meanwhile, a multi-billion-dollar business involving angioplasty and countless related knifeless procedures burst into life, often overshadowing the noble quest for innovation with a race for profit.--From publisher description.
Keywords: Cardiology -- History; Heart -- Endoscopic surgery -- History; Cardiology -- Biography; Cardiology -- history; History, 20th Century; Thoracic Surgery -- history